Connecting OER With Mandatory Textbooks in an EFL Classroom: A Language Theory–Based Material Adoption - Zhang, Xiaodong (International Review of Research in Open and Distributed Learning, 2018)
Systemic functional linguistics (SFL) theory focuses on developing language learners’ meta-linguistic understanding of the interrelation among linguistic form (grammar/vocabulary), meaning, and context. Guided by SFL when using a mandatory textbook and open educational resources, this study investigates how exposure to this blended teaching and learning context may impact English-as-a-foreign-language (EFL) learners’ adjustment to materials used in their learning, as well as their learning practices. By drawing on the written documents of four students written, and on interviews conducted with these students over an academic semester in an EFL writing course, this qualitative study, through content analysis and discourse analysis, shows that the SFL theory-based material adoption did a good job of supporting EFL students in their internalization of language knowledge from both open educational resources and traditional textbooks, while also enabling students to use materials flexibly instead of passively following along with the content in the mandatory textbook. The flexibility of the students participating in the study was particularly reflected by their ability to construct principled knowledge informed by SFL and to independently apply such knowledge to effectively navigate literacy practices (e.g., critical construction and deconstruction of discourses).